Effect of Modified Compound Xiaozhang Powder for Patients with Shoulder-Hand Syndrome after Cerebral Infarction by Using Fumigation and Washing combined with Acupuncture - Dujuan GE; Liyu WU; Sanfeng SUN; Xiangshu LI (康复学报)
Objective:To observe the clinical efficacy of modified compound Xiaozhang powder by fumigation and washing combined with acupuncture in the treatment of shoulder-hand syndrome after cerebral infarction.Methods:Eighty patients with shoulder-hand syndrome after cerebral infarction were selected in Huairou District Hospital of Traditional Chinese Medicine. The patients were randomly divided into control group (n=40) and observation group (n=40). The control group was given routine medical treatment and rehabilitation training. Rehabilitation training 20-30 min a time, one time per day, five times per week, continuous treatment for one month. The observation group was treated with modified compound Xiaozhang powder by using fumigation and washing combined with acupuncture on the basis of the control group. Fumigation and washing treatment: modified compound Xiaozhang powder plus water decoction, leaving 1 500-2 000 mL of traditional Chinese medicine decoction, put into a constant temperature bucket, when the water temperature is reduced to 40-50℃, put the hemiplegic swollen hand in the medicine solution, while soaking, dipping liquid from the elbow to the wrist while rubbing to knead to the interphalangeal joint,20 minutes a time, two times per day, five days per week, continuous treatment for one month. Acupuncture treatment: using Xingnaokaiqiao acupuncture method to acupuncture at Jiquanxia, Chize, Neiguan acupoint, without leaving needle; acupuncture at Jianyu, Jianliao, Quchi acupoint, directly needling 0.5-1 inch, twisting and tonifying method for one minute, retaining needle 20 minutes a times, once a day, once every other day, three times a week, continuous treatment for one month. The upper limb motor function was evaluated by the Fugl-Meyer motor function rating scale (FMA-U), the activities of daily living was evaluated by the Modified barthel index (MBI), the pain degree of the affected limbs was evaluated by the pain visual analogue scale (VAS), the shoulder range of motion (ROM) was measured by protractor, and the degree of hand edema was measured by drainage method.Results:Compared with before treatment, FMA-U, MBI and shoulder range of motion in the two groups after treatment for one month increased significantly, while VAS score and the degree of hand edema difference decreased significantly, and the difference was statistically significant (P<0.05). Compared with the control group, the FMA-U, MBI, shoulder ROM of the observation group after treatment for one month were significantly higher, the VAS score and the degree of hand edema difference in the observation group were significantly lower, and the difference was statistically significant (P<0.05). The total effective rate in the observation group (92.5%) was significantly higher than that in the control group (67.5%), and the difference was statistically significant (P<0.05).Conclusion:Modified compound Xiaozhang powder by using fumigation and washing combined with acupuncture can effectively improve the degree of hand swelling and relieve pain of patients with shoulder-hand syndrome after cerebral infarction, improve upper limb motor function, shoulder ROM and activities of daily living, and it has a good curative effect.